The ionic composition of aerosol in Big Bend National Park - Lee, Taehyoung, author; Collett, Jeffrey L., Jr., author; Cooperative Institute for Research in the Atmosphere (Fort Collins, Colo.), publisher (Colorado State University. Libraries, 2002)
The chemical compositions of PM2.5 and size-resolved aerosol particles were measured from July to October, 1999 in Big Bend National Park, Texas, during the Big Bend Regional Aerosol and Visibility Observational (BRAVO) Study. Daily PM2.5 samples were collected using a URG cyclone/annular denuder/filter pack sampling system consisting of a PM2.5 cyclone inlet, two coated annular denuders in series (for nitric acid and ammonia), and a filter pack. Aerosol particles collected on a Teflon filter were analyzed for major ions and a backup nylon filter was used to capture nitric acid volatilized from the collected particles. A Micro Orifice Uniform Deposition Impactor (MOUDI) was used to collect 24 hr size-resolved aerosol particle samples in 9 size categories (D50 = 18, 10, 5.6, 3.2, 1.8, 1.0, 0.56, 0.32 and 0.18 μm). 41 MOUDI sample days were selected for analysis of the ionic chemical composition as a function of particle size. PM2.5 and size-resolved aerosol concentrations of C1-, SO42-, NO3-, Na+, NH4+, K+, Mg2+, and Ca2+ were obtained through ion chromatographic analysis of the filter and impactor samples. Aerosol acidity was measured on-site in the daily PM2.s filter samples. The composition of the BRAVO PM2.5 aerosol was dominated by sulfate and ammonium. Daily average sulfate and ammonium concentrations were strongly correlated (R2=0.97). The ratio of ammonium to sulfate averaged 1.54 with standard deviation of 0.30. This ratio is consistent with the direct pH measurements of aerosol acidity. The highest concentrations of sulfate were observed from August to October, reaching as high as 8.5 μg/m3. Back-trajectories suggested long-range transport from regions along the Texas/Mexico border and east Texas was associated with peak sulfate concentrations in the park. The particle composition as a function of size obtained from the MOUDI samples suggests that most of the particulate nitrate is associated with coarse mode particles in the range of 4 - 5 μm diameter. Aerosol nitrate concentrations were correlated with the sum of aerosol Na+ and Ca2+ concentrations (R2 = 0.70 and 0.60 for MOUDI and URG, respectively), demonstrating the importance of sea salt and soil dust particles in providing non-acidic surfaces for the condensation of nitric acid. The MOUDI samples indicate that nitrate and sulfate are separated into supermicron (mode diameter 4 - 5 μm) and submicron (mode diameter 0.4 - 0.5 μm) particles, respectively. The MOUDI samples show that a 1 μm size cut would have provided a better division between the fine mode and the coarse mode aerosol during the BRAVO study. Comparison of ISORROPIA and SCAPE2 thermodynamic model predictions of solid phase sulfate species shows reasonable agreement between the models, although ISORROPIA sometime predicts higher concentrations of some species. ISORROPIA often predicts the presence of solid phase Na2SO4, while SCAPE2 seldom does. The difference between solid phase sulfate concentrations predicted by the two models largely reflects differences in predicted aerosol water content. Both models reasonably predict the observed phase partitioning of N(-III) but poorly predict the observed phase partitioning of N(V). The underprediction of aerosol nitrate by these bulk aerosol models reflects the fact that the PM2.5 aerosol is externally mixed, containing acidic submicron sulfate particles and supermicron nitrate particles.
July 2002.
Keywords: Aerosols -- Measurement; Air -- Pollution -- Texas -- Big Bend National Park; Visibility -- Texas -- Big Bend National Park